2009
DOI: 10.1007/s00482-009-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss von Akupunktur auf postoperative Schmerzen, Übelkeit und Erbrechen nach viszeralen Eingriffen

Abstract: Repeated needle acupuncture may be effective in postoperative pain relief and the treatment of nausea and vomiting in the postoperative period. These effects seem not to be due solely to interaction between the acupuncturist and the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, the intestinal gas, bloating, and stool consistency composite score exhibited a similar pattern of improvement [ 127 ]. For postoperative pain due to visceral surgery, acupuncture can effectively reduce the pain, lower analgesic consumption, and improve other symptoms like nausea and vomiting [ 128 ]. Interestingly, a study conducted in healthy subjects showed that acupuncture transcutaneous electrical nerve stimulation, a noninvasive modality of procedure, could enhance the perception (distention, defecation, discomfort, and pain) threshold in comparison with the placebo controls.…”
Section: Management Of Pain and Visceral Pain By Acupuncturementioning
confidence: 99%
“…In addition, the intestinal gas, bloating, and stool consistency composite score exhibited a similar pattern of improvement [ 127 ]. For postoperative pain due to visceral surgery, acupuncture can effectively reduce the pain, lower analgesic consumption, and improve other symptoms like nausea and vomiting [ 128 ]. Interestingly, a study conducted in healthy subjects showed that acupuncture transcutaneous electrical nerve stimulation, a noninvasive modality of procedure, could enhance the perception (distention, defecation, discomfort, and pain) threshold in comparison with the placebo controls.…”
Section: Management Of Pain and Visceral Pain By Acupuncturementioning
confidence: 99%
“…Multiple studies have also shown that acupuncture may be cost effective for chronic headaches (including migraines), low back pain and osteoarthritis pain [1217]. In the inpatient setting, the use of adjunctive acupuncture has been shown to reduce pain, nausea, and vomiting and decrease the need for narcotic use [18, 19]. To date, however, no randomized controlled trials have examined acupuncture's acceptance in the inpatient hospital setting or effectiveness in reducing associated costs and length of stay.…”
Section: Introductionmentioning
confidence: 99%